Toll-like receptors as diagnostic targets in pellucid marginal degeneration - Regueiro, Uxía; Pérez-Mato, María; Hervella, Pablo; Campos, Francisco; Sobrino, Tomás; Lema, Isabel (Experimental eye research, 2020)
The main purpose of this study is to evaluate the diagnostic role of Toll-like receptors 2 (TLR2) and 4 (TLR4) expression in corneal and conjunctival epithelial cells of eyes with pellucid marginal degeneration (PMD) compared to keratoconus patients (KC) and control subjects. A prospective case-control study in 29 PMD eyes, 109 KC eyes and 72 healthy eyes was done. All participants were subjected to a clinical, topographic, aberrometric and tomographic exam with extraction of corneal and conjunctival epithelial cells through scraping. The TLR2 and TLR4 expression was measured with flow cytometry. Receiver operating characteristic (ROC) curve analysis was used to determine the most appropriate cutoff point for predicting the risk of PMD and KC. Correlations between TLR2/TLR4 expression and the severity of PMD/KC were evaluated. A TLRs follow-up review was made 19 ± 4 months after to the first review. As result, mean expression of TLR2 and TLR4 in both corneal and conjunctival epithelial cells was significantly higher in eyes with corneal ectasia (PMD and KC) than in control eyes (all p < 0.05). Conjunctival TLR4 expression showed the highest capacity to diagnose the existence of PMD (odd ratio 42.84; 95% confidence interval:6.20–296.20; p < 0.0001) after adjusting by eye rubbing and steeper corneal meridian. Moreover, we found an association between the TLR2/TLR4 overexpression with the severity of the PMD and KC measured by corneal topographic, aberrometric and tomographic quantitative parameters (all p < 0.05). Differences on TLR2/TLR4 expression between study groups were maintained during the follow-up period. In conclusion, the TLR2/TLR4 overexpression in corneal and conjunctival epithelial cells of PMD and KC patients compared to healthy control subjects have demonstrated their role as diagnostic target in both corneal ectatic disorders. [Display omitted] •Corneal and conjunctival TLR2/TLR4 are overexpressed in eyes with PMD and KC.•Both TLR2/TLR4 constitute important diagnostic biomarkers for eyes with PMD/KC.•The TLR2/TLR4 overexpression is correlated with the disease severity.•TLR2/TLR4 overexpression in PMD/KC were maintained in the follow-up review.